Layout optimization of crushing station in open-pit mine based on two-stage fusion particle swarm algorithm. Issue 10 (3rd October 2021) - Gu, Qinghua; Li, Xuexian; Chen, Lu; Lu, Caiwu
Abstract : In the production process of open-pit mines, transportation costs account for 45–60% of the total cost. Therefore, a reasonable and economic transportation system can effectively improve production efficiency. In this article, optimization of the layout of the fixed crushing station in the in-pit crusher and conveyor system of open-pit mining is studied. First, the entire ore body is discretized into multiple ore blocks. By calculating the transportation distance between each block and the crushing station, an optimized model for minimizing the total transportation work is established. Finally, combining the advantages of particle swarm optimization (PSO) and quantum PSO (QPSO), a two-stage fusion particle swarm optimization algorithm (TSF-PSO) is designed to solve the model, and the effectiveness of the model is verified by actual cases. Experimental data show that, compared with the PSO and QPSO algorithms, the solution efficiency of the TSF-PSO algorithm is improved by 2.83% and 1.48%, respectively.